CORRELATION BETWEEN CARDIOMEGALY AND PULMONAL DYSFUNCTION IN CHRONIC HEART FAILURE - Sutedjo, Isbianto (Acta Interna The Journal of Internal Medicine, 2012)
ABSTRACTBackground: Cardiac enlargement or cardiomegaly always found in chronic heart failure (CHF). Progressivity of cardiac enlargement relates with pulmonal function changes in CHF. This study examined the influence of increased cardiac enlargement on pulmonal function.Methods: This is a cross sectional study on 63 CHF patient of New York heart Association (NYHA) class I and II that fulfilled inclusion criteria. Definitions of CHF based on Framingham criteria. Cardiac enlargement measured by Danzerâs methods through postero anterior chest radiography. Spirometry used to evaluate FVC and FEV1.Results: Male subjects have an equal proportion (49.21%) with female subjects (50.79%) with mean of CTR 59.47 Â± 5.57%. Spirometry test showed mean predicted FVC (%) 61.83 Â± 9.62, predicted FEV1 (%) 75.27 Â± 12.55, and FEV1/FVC mean ratio 95.53 Â± 2.19%. Coefficient correlations between cardiomegaly and FVC (%) and FEV1 (%) predicted are -0.537 (p <0.001) and -0.460 (p <0.001). duration of diseased has a negative correlation with FVC (%) and FEV1 (%) predicted (-0.329; p= 0.008 and -0.341; p=0.006).Conclusions: Cardiomegaly on CHF showed a restriction type and has a negative correlation with pulmonal function.Â Keywords: cardiomegaly, pulmonal dysfunction, chronic heart failure